Pengaruh Pembelajaran Literasi Terhadap Keterampilan Membaca Pemahaman Siswa Kelas IV MI At Taufiq Pekkae - Fajria Riski Yuliana; Syahruddin Syahruddin; Haslinda Haslinda (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The main problem in this research is the lack of reading comprehension skills in grade IV students. This research aims to determine the effect of literacy learning on fourth grade students' reading comprehension skills. The type of research used was experimental with a One Group Pretest-Posttest research design. The data source in this research was 21 class IV students. Data collection was carried out using the results of the reading comprehension skills assessment. The data obtained was then analyzed using statistical analysis techniques, namely descriptive statistics and inferential statistics. After analyzing the data, the results of hypothesis testing obtained a comparison of the Pre-test results, namely 82.76 and Post-test, namely 93.714, which shows that the value of tCount = 5.8099 and tTable = 2.08596, so tCount ≥ tTable or 5.8099 ≥ 2.08596 so it can be concluded that H0 is rejected and H1 is accepted. This means that literacy learning on students' reading abilities has an influence in improving fourth grade students' reading comprehension abilities.